Strategi Pengelolaan Destinasi Wisata Pantai Papuma Berbasis Arsitektur Ekologis untuk Mendukung Pariwisata Berkelanjutan - Hablana Rizka; Firda Diartika; Tri Rafika Diyah Indartin (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
Papuma Beach is one of the leading natural tourism destinations in Jember Regency, with significant potential to support Indonesia’s national tourism development programs, which emphasise the sustainable utilisation of coastal areas. In developing this nature-based tourism potential, spatial planning strategies are required that go beyond aesthetic and functional considerations, incorporating environmental sustainability and disaster risk mitigation. These strategies must also address the conservation of natural resources and the preservation of local values. This study aims to formulate a management and spatial planning strategy for the Papuma Beach area, based on the principles of ecological architecture, with a focus on optimising local potential while preserving ecological integrity. The research was conducted in the Papuma Beach area, which has been designated as a priority tourism destination in Jember Regency. A qualitative descriptive approach was employed, utilising data collection techniques such as field observations, stakeholder interviews, and comparative analyses of theoretical frameworks and relevant policies. The findings of this study present a spatial planning strategy that is adaptive to local characteristics, respects the cultural values of the surrounding community, and integrates environmental conservation principles, laying a foundation for the realisation of a sustainable tourism destination.